Fenomena Keikutsertaan Isteri Dalam Pemenuhan Nafkah Perspektif Hukum Islam - Naseh, Ahmad Muhammad (Mabahits : Jurnal Hukum Keluarga Islam, 2024)
Islam has divided the roles of husband and wife in the household in detail. This includes the task of fulfilling family finances (breadwinner), where this is the responsibility of the husband, while the wife is obliged to regulate the domestic sector in the household. However, the reality exists, many wives participate in the task of financial maintenance. This phenomenon is important to continue to discuss because disputes over duties in the household will have an impact on life together. This research is a library research with a qualitative approach and uses a content analysis methodology. This research aims to reveal the phenomenon of wife's participation in the fulfillment of family support, such as factors, impacts, and reviews of Islamic law. This research produces the phenomenon of wife's participation in the task of family finances has several factors, internal from the wife's own personal self and external factors that cause a wife to need to do it. This phenomenon also has positive and negative impacts that affect the lives of married couples, children, and families. Meanwhile, according to a review of Islamic law, the participation of the wife in the fulfillment of the maintenance which is the husband's duty is allowed but with several conditions. The most important requirement is to maintain her main duties as a wife and housewife.